Islamic Law Paradigm Responding Conflicts of Interest of Economic Development and Ecological Conservation Hifdz al-Bi'ah Perspective - Rois, Choirur; Jannani, Nur; Mufid, Moh. Hoirul (Institut Agama Islam Negeri Curup, 2024)
This research is aimed to examine the policy paradigm and alignments of the Indonesian government in responding to conflicts of interest in economic development and environmental preservation from the perspective of hifdz al-bi'ah theory and the rules of fiqh taá¹£arruf al-imÄn 'ala al-ra'iyah manutun bi al-maslahah. Many polemics on strategic government projects such as the construction of Rempang Eco-City and several similar cases were used as study material. The research used descriptive qualitative methods focused on literature study. The analytical method used inductive descriptive techniques involving legislative approaches, Islamic law, and the theory of hifdz al-bi'ah which originates from the maqashid sharia discourse. The conclusion of this research shows that the interests of environmental preservation must receive priority in every government development policy. The effort of government to accelerate the pace of development must not conflict with aspects of environmental sustainability. The interest in preserving the environment is universal in terms of Islamic legal, socio-cultural, economic, and political norms. The implications of this research emphasize that if the government policy paradigm and development program has the potential to threaten the sustainability of environmental conservation, thus on the basis of welfare the government is not justified in establishing policies that are contrary to the interests of ecological empowerment, either in the form of long-term or medium-term development plans, especially in downstream programs industries that are projected to boost the national economic progress.